PENGARUH PROFITABILITAS, DEBT TO EQUITY RATIO, KUALITAS AUDITOR, DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2012-2015) - WIJAYANTI, (Jurnal Akuntansi AKUNESA, 2017)
The purpose of this research is to analyze the influence of Profitability, Debt to Equity Ratio, Auditor Quality, and Company Size on Financial Reporting Timeliness. The sample is manufacturing companies listed on the Indonesian Stock Exchanges from 2012-2015, and using purposive sampling, the total final sample is 209 companies. This study uses secondary data such as audited financial statements. Using Logistic Regression analysis, the results show that profitability, measured by ROA, has  significant effect on  reporting timelines, meanwhile other independent variables, such as Debt to Equity Ratio (DER), auditor quality and firm size have no effect on financial reporting timelines.   Keywords: auditor quality, debt to equity ratio, firm size, profitablity, reporting timeliness